2021
DOI: 10.3390/cancers13194864
|View full text |Cite
|
Sign up to set email alerts
|

AXL Receptor in Cancer Metastasis and Drug Resistance: When Normal Functions Go Askew

Abstract: The TAM proteins TYRO3, AXL, and MER are receptor tyrosine kinases implicated in the clearance of apoptotic debris and negative regulation of innate immune responses. AXL contributes to immunosuppression by terminating the Toll-like receptor signaling in dendritic cells, and suppressing natural killer cell activity. In recent years, AXL has been intensively studied in the context of cancer. Both molecules, the receptor, and its ligand GAS6, are commonly expressed in cancer cells, as well as stromal and infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 128 publications
0
27
0
Order By: Relevance
“…It was observed that Gas6 is frequently overexpressed in lung cancer cells and is found in the plasma [ 42 , 43 ], and Gas6 is associated with cell growth of stromal cancerous cells and tumor progression [ 44 ]. Therapeutic agents targeting Gas6 and AXL have been developed, and promising results have been observed in both preclinical and clinical settings when such agents are used alone or in combination [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that Gas6 is frequently overexpressed in lung cancer cells and is found in the plasma [ 42 , 43 ], and Gas6 is associated with cell growth of stromal cancerous cells and tumor progression [ 44 ]. Therapeutic agents targeting Gas6 and AXL have been developed, and promising results have been observed in both preclinical and clinical settings when such agents are used alone or in combination [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of TGF-β in tumor cells exerts dual effects: regulating the expression of PD-L1 and VEGF and affecting biomarkers associated with the modulation of immune response and evasion, including Foxp3/Treg, MDSC, Th1/Th2 balance, and macrophage cells [ 9 , 10 , 17 , 18 , 19 , 49 , 56 , 57 , 58 ]. HIFs and TGF-β are biomarkers associated with the expression of the AXL gene, which is highly overexpressed in tumors with a loss of VHL function and is associated with a poor response to biologically targeted molecules [ 59 , 60 , 61 , 62 , 63 ]. Based on published data generated by others and data generated in our laboratory, Figure 4 is presented to illustrate the potential role of miR-210, miR-155, TGF-β, and HIFs individually or collectively in the regulation of multiple targets.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, AXL contribute to epithelial plasticity programs in mammary stem and progenitor cells, and, when co-opted, maintains acquired stemness in BCa cells. It is well documented that AXL is particularly important for persister cells ( 119 ). Shaffer and colleagues demonstrated that human melanoma cells exhibit profound transcriptional variability at the single-cell level.…”
Section: Axl and Epithelial-mesenchymal Plasticitymentioning
confidence: 99%
“…Due to the pro-tumoral, pro-metastatic, and treatment resistance roles of AXL, numerous therapeutic interventions targeting AXL have been designed and investigated. Several investigators have covered this topic well to which the readers can be referred ( 7 , 21 , 22 , 30 , 36 38 , 53 , 119 , 172 , 195 ).…”
Section: Toward Standardization Of Axl-targeting Agents In Combinatio...mentioning
confidence: 99%